Between Empire and Mountain: Monk An Daoyi, Cliff Sutra Inscriptions, and The Localization of Buddhism in Northern Dynasties Shandong (386-581 CE) - Zhang, Changlong; Gotiram, Chompoo (Prosiding University Research Colloquium, 2026)
This article examines the localization of Buddhism in Northern Dynasties China (386-581 CE) through a focused case study of the monk An Daoyi (???) and the cliff sutra inscriptions associated with his activities in Shandong Province. Moving beyond state-centered narratives that privilege imperial patronage and official Buddhist institutions, the study foregrounds regional monastic agency and material religious practice as critical forces shaping Buddhist transmission. Drawing on epigraphic evidence, historical texts, spatial analysis, and social network reconstruction, the article analyzes how An Daoyi mobilized local elites, monastic networks, and sacred landscapes to inscribe Mah?y?na doctrine-particularly Prajñ?p?ramit? thought-directly into mountainous terrain. The findings demonstrate that An Daoyi functioned as a monastic intermediary, mediating between imperial Buddhist orthodoxy and local religious ecologies shaped by mountain worship, gentry patronage, and sociopolitical instability. His cliff inscriptions operated simultaneously as textual transmissions, ritual technologies, and spatial interventions, transforming natural landscapes into enduring Buddhist sacred spaces. This bottom-up model of localization challenges dichotomous interpretations of "imperial versus popular Buddhism" and reveals how Buddhist authority was negotiated through materiality, calligraphy, and place-based devotion. By integrating theories of regional religion, social networks, and religious materiality, this article contributes to broader debates on Buddhist localization in medieval China. It offers a methodological framework for studying how religious traditions are reconfigured through localized monastic action beyond imperial centers.